Perancangan Development Cycle Over The Air pada Sistem IoT berbasis Teknologi Container - Rifki Karim Ramadhan; Sabriansyah Rizqika Akbar; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
The development of Internet of Things (IoT) systems using container technology has several problems, such as difficulty in managing and updating deployed applications, and difficulty in managing dynamically changing system configurations. To solve these problems, a development method is needed that can help manage and update IoT system applications using container technology. This method is called the Development Life Cycle Over the Air (DLCOTA). DLCOTA is a development method that allows the automatic and controlled deployment, update, and rollback of IoT system applications through the internet. The design of the Development Cycle for the IoT system using the Development Life Cycle Over The Air (DLCOTA) method adapts the software development method of Continuous Integration Continuous Delivery (CI/CD), Continuous Integration Continuous Delivery is a system that uses automation techniques to speed up and simplify the development process of the Internet of Things (IoT) system. Automation of Continuous Integration (CI) and Continuous Delivery (CD) is a method that can be used to improve the efficiency and reliability of IoT system development. The result of the DLCOTA design is a system that is able to perform the automatic and controlled deployment, update, and rollback of IoT system applications through the internet. This system is also able to manage dynamically changing system configurations and improve system reliability and security. In addition, this research will test the utility of using computational resources on the Raspberry Pi